2010
DOI: 10.1007/978-3-642-15141-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Disintermediation in the Tourism Industry: Theory vs. Practice

Abstract: It has been several decades since disintermediation was first known (although under other terms), and it seems that disintermediation has become increasingly intense, particularly in the tourism industry where many large hotels and airlines have successfully utilized the Internet and website as a direct channel to sell to their customers. This paper examines disintermediation issues and situation and argues that in practice disintermediation, despite becoming increasingly intense, it will just require travel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…An interesting study on possible disintermediation of TAs in Thailand was conducted by Kaewkitipong (2010). Although disintermediation of TAs in travel industry is real, especially in the USA and Europe, disintermediation of TAs in Thailand is not as extreme as in the USA and Europe although many small and medium size hotels have offered direct reservations through their web sites.…”
Section: Ireservation Systemmentioning
confidence: 99%
“…An interesting study on possible disintermediation of TAs in Thailand was conducted by Kaewkitipong (2010). Although disintermediation of TAs in travel industry is real, especially in the USA and Europe, disintermediation of TAs in Thailand is not as extreme as in the USA and Europe although many small and medium size hotels have offered direct reservations through their web sites.…”
Section: Ireservation Systemmentioning
confidence: 99%
“…This is considered as a key in driving reservations directly to hotels’ websites without the need for intermediaries, as hotels are able to offer consumers rooms and packages directly via social media. Nevertheless, even if it is demonstrated that positive comments on social media can improve consumers’ attitudes toward hotels (Kaewkitipong, 2010), the tourism and hospitality industry continues to struggle with incorporating online interactive tools into their distribution strategy (Law et al ., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is considered key in driving reservations directly to hotels' websites without the need for intermediaries, as hotels are able to offer consumers rooms and packages directly via social media. Nevertheless, even if it is demonstrated that positive comments on social media can improve consumers' attitudes towards hotels (Kaewkitipong, 2010), the tourism and hospitality industry continues to struggle with incorporating online interactive tools into their distribution strategy (Law et al, 2015). Ho et al (2016) explored the use of pre-trip smartphone information searches and found that mobiles continue to be used very often simply as browsers to gather information, while, increasingly, apps are launched that integrate information search and access.…”
Section: Social Media Online Review Sites and Mobile Bookingsmentioning
confidence: 99%
“…Este nuevo paradigma implica un nuevo contexto de competencia y el establecimiento de nuevas relaciones a través de la creación de valor en la cadena de suministro (proveedores, productores, distribuidores y consumidores). Esta situación comenzó con la ruptura de la cadena de suministro tradicional a través de la desintermediación y la operación directa de negocios entre productores y clientes (business to consumer), eliminando la figura del intermediario/mediador de la red configurada por los proveedores-intermediario-consumidores (Kaewkitipong, 2010).…”
Section: Introductionunclassified